Four-octyl itaconate activates Keap1-Nrf2 signaling to protect neuronal cells from hydrogen peroxide - Hua Liu; Yu Feng; Min Xu; Jian Yang; Zhichun Wang; Guangfu Di (Cell Communication and Signaling, 2018)
Abstract Background Four-octyl itaconate (OI), the itaconate’s cell-permeable derivative, can activate Nrf2 signaling via alkylation of Keap1 at its cysteine residues. The current study tested the potential neuroprotective function of OI in hydrogen peroxide (H2O2)-treated neuronal cells. Methods SH-SY5Y neuronal cells and epigenetically de-repressed (by TSA treatment) primary murine neurons were treated with OI and/or H2O2. Nrf2 pathway genes were examined by Western blotting assay and real-time quantitative PCR analysis. Neuronal cell death was tested by the LDH and trypan blue staining assays. Apoptosis was tested by TUNEL and Annexin V assays. Results In SH-SY5Y neuronal cells and primary murine neurons, OI activated Nrf2 signaling, causing Keap1-Nrf2 disassociation, Nrf2 protein stabilization and nuclear translocation, as well as expression of Nrf2-regulated genes (HO1, NQO1 and GCLC) and ninjurin2 (Ninj2). Functional studies showed that OI attenuated H2O2-induced reactive oxygen species (ROS) production, lipid peroxidation and DNA damage as well as neuronal cell death and apoptosis. shRNA-mediated knockdown, or CRISPR/Cas9-induced knockout of Nrf2 almost abolished OI-induced neuroprotection against H2O2. Keap1 is the primary target of OI. Keap1 knockout by CRISPR/Cas9 method mimicked and abolished OI-induced actions in SH-SY5Y cells. Introduction of a Cys151S mutant Keap1 in SH-SY5Y cells reversed OI-induced Nrf2 activation and anti-H2O2 neuroprotection. Conclusions OI activates Keap1-Nrf2 signaling to protect SH-SY5Y cells and epigenetically de-repressed primary neurons from H2O2 in vitro.